If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(x + 7) = -40 Reorder the terms: -5(7 + x) = -40 (7 * -5 + x * -5) = -40 (-35 + -5x) = -40 Solving -35 + -5x = -40 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '35' to each side of the equation. -35 + 35 + -5x = -40 + 35 Combine like terms: -35 + 35 = 0 0 + -5x = -40 + 35 -5x = -40 + 35 Combine like terms: -40 + 35 = -5 -5x = -5 Divide each side by '-5'. x = 1 Simplifying x = 1
| 6x+15y=6 | | 21-4x=45 | | -10(x+1)=10 | | -2x^4+4x^3=0 | | 9(x-15)=9 | | 32-6x=53 | | 9x+4=14-3 | | 0=16x+32000 | | 10-2(3-4x-4)-(3x-4-2)= | | 8x=5x-4 | | 9x-19=5x-3 | | 15-5w=-75-10w | | -15-5w=-75-10w | | y=2(-9)+11 | | -15-5w=75-10w | | x+(x+24)+(4x-36)=1152 | | (2x+11)=-2x-25 | | 21x+6=4 | | x^2+22x-46=0 | | 24=-18-3x | | (4a+7)(8a^2-3a+2)= | | x+20+x=46 | | 70y(2)+40x(1.5)=34000 | | x+8.5+x=727.5 | | (-1)-y=4 | | (0)-y=4 | | 5x^2+4x-40=0 | | 5x^2+4-40=0 | | -11+10p+100=4-10p-55 | | 16x+8(-2x-6)=-48 | | 9x+5y=8 | | 80y(2)+50x(1.5)=63000 |